GAMBARAN EPIDEMIOLOGI PENDERITA INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS TELADAN KECAMATAN MEDAN KOTA TAHUN 2016 - Mega Olivia S; Jemadi .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Health development in 2015-2019 period is Indonesia Sehat Programwith the goal of improving the health status and nutritional status of the community through health efforts and community empowerment. One of the main object of the health development is the increasing of disease control including acute respiratory infection. Acute respiratory infections is the main cause of morbidity and mortality by an infectious disease among children under five years. Acute respiratory infections is still a major health issue in Indonesia. To find out the epidemiological description of acute respiratory disease among children under five years in the working area of Puskesmas Teladan in 2016, has been done a descriptive research with series design. The population are 253 children and the sample are 155 children. Patients with acute respiratory infections most commonly found in not pneumonia category (85,2%), the most in the age group 12-36 months (42,0%), male has the highest proportion (53,5%), malnutritional status has the highest proportion (36,1%), March has the highest proportion (12,3%), incomplete immunization status has the highest proportion (56,8%), outside the working area of Puskesmas Teladan has the highest proportion (32,3%). The result of chi square analysis showed that there was no difference between the proportion of acute respiratory infections classification by age (p=0,824), nutritional status (p=0,668), residence (p=0,839), there was no difference between proportion of nutritional status by age group (p=0,313). However, there is a difference between the proportion of acute respiratory infections classification based on immunization status (p=0,014). From the result of this study, it is known that there should be a program to deliver information to the public about the risks, causing factors and how to prevent acute respiratory infection in children under five years so that the morbidity and mortality can be reduced. Key Words : Acute respiratory infections, Acute respiratory infections in children under five years